Enterococcus gallinarum meningitis: a case report and literature review - Fahmi Yousef Khan; Sitina Shamsaldin Elshafi (Journal of Infection in Developing Countries)
We report a case of Enterococcus gallinarum meningitis in a 53-year-old female who was admitted to our hospital with a fever, headache, and consciousness disturbance one week after a life-saving craniotomy operation. There was obvious neck stiffness; lumber puncture was performed and cerebrospinal fluid parameters were consistent with bacterial meningitis. The patient was given ceftriaxone and vancomycin for bacterial meningitis. Cerebrospinal fluid culture yielded an isolate which was identified as Enterococcus gallinarum. The isolate was sensitive to ampicillin, ampicillin/clavulanate, linezolid, moxifloxacin and teicoplanin, but it showed intermediate sensitivity to vancomycin and quinoprism- dalfopristin. Intravenous linezolid, 600 mg every 12 hours, was started. Three days after starting treatment, the patient became afebrile; a repeat lumber puncture two week later showed no white blood cells in cerebrospinal fluid and no bacterial growth. Treatment with linezolid was continued for a total therapy duration of three weeks, after which the patient was discharged in a good condition.